1997
DOI: 10.1046/j.1472-765x.1997.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis of Lactobacillus plantarum to monitor lag times, cell divisionand injury

Abstract: . 1997. Flow cytometry in combination with fluorescent molecular markers 5-(and 6-) carboxyfluorescein succinimidylester (CFSE) and propidium iodide (PI) have been applied to determine lag times, numbers of cell divisions and injury after mild heat (50°C, 5 min) and nisin treatments (0·1 and 1·0 mg ml −1 ) of Lactobacillus plantarum. Initial labelling with covalently bound dye CFSE (20 and 100 mg ml −1 ) allowed determination of lag times and cell proliferation for up to eight generations. Double-labelling wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 1 publication
1
52
0
Order By: Relevance
“…Discrimination between intact and permeable cells by fluorescent stains has been used in many studies on bacteria, including a few recent applications on lactic acid bacteria. Injury of Lactobacillus plantarum by nisin treatment was observed with PI and carboxyfluorescein succinimidylester using FCM (28). Furthermore, the membrane permeability of L. lactis was measured with PI and carboxyfluorescein diacetate (cFDA) using spectrofluorimetry and fluorescence microscopy in a study of viability after various stress treatments (6).…”
Section: Discussionmentioning
confidence: 99%
“…Discrimination between intact and permeable cells by fluorescent stains has been used in many studies on bacteria, including a few recent applications on lactic acid bacteria. Injury of Lactobacillus plantarum by nisin treatment was observed with PI and carboxyfluorescein succinimidylester using FCM (28). Furthermore, the membrane permeability of L. lactis was measured with PI and carboxyfluorescein diacetate (cFDA) using spectrofluorimetry and fluorescence microscopy in a study of viability after various stress treatments (6).…”
Section: Discussionmentioning
confidence: 99%
“…The flow cytometry profile showed that about 99% of the cells were labeled. A doubling in the cell concentration resulted in reduction of the median fluorescence intensity to half (9,17). Thus, the generation time (t d ) could be determined from the fluorescence intensity of the cells as t d ϭ ln2 ϫ (time interval)/(change in ln fluorescence intensity), where ln is the natural log value.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular Ca 21 levels were measured by flow cytometry as described (24). ZG cells were loaded with 2 mM Fluo-4-AM for Fig.…”
Section: Determination Of Intracellular Ca 21 Levelsmentioning
confidence: 99%